Protection of the Earth as a Unique Life Form: Philosophical and Legal Analysis in the Context of the Pandemic - Anisimov, Alexey; Ryzhenkov, Anatoliy (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
The article presents a philosophical and legal analysis of the concept of the Earth as a living organism in the context of modern international environmental law. The article argues for the need for a fundamental rethinking of the environmental law concept in terms of the global environmental and pandemic crises on the basis of an in-depth study of the Gaia hypothesis of James Lovelock, the concepts of the biosphere and noosphere proposed by Vladimir Vernadsky as well as the ideas of Lynn Margulis, Dorion Sagan and other authors. The emphasis is placed on the philosophical aspects of international and national law related to the transition from the anthropocentric to the ecocentric paradigm. It is substantiated that it is necessary to recognize the Earth as a unique life form having its own interests and value that do not depend on man. The authors note that the coronavirus pandemic, the climate crisis and other global challenges require the international community to form a new philosophical and legal paradigm based on respect for the integrity of the biosphere and the understanding of the interdependence of man and nature.